PERENCANAAN ARSITEKTUR SISTEM INFORMASI NOTARIS MENGGUNAKAN ENTERPRISE ARCHITECTURE PLANNING PADA KANTOR NOTARIS ANI YANIATIN PITALOKA, S.H. - Hidayat, Topik; Dwicahya Supriatman, Rian; Sidiq, Maulana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
Digitalization is crucial for all sectors, including notary offices. This study evaluates the implementation of Enterprise Architecture Planning (EAP) to design an efficient information system at the Notary Office of Ani Yaniatin Pitaloka, S.H. in Pangandaran Regency. The aim is to create a comprehensive information system architecture design that aligns with business strategies and implementation steps. Using the four EAP stages Initiation, Current State Understanding, Future Planning, and Achievement Strategy the study improves manual processes with an integrated system based on a star topology. The resulting blueprint provides an implementation guide for notarial service applications and document archiving.